Minimally invasive esophagectomy for carcinoma esophagus- outcome of surgical management: a single centre experience - Jakhmola, C. K.; Trehan, Vikram; Kumar, S. Santosh (International Surgery Journal, 2018)
Background: Minimally invasive esophagectomy (MIE) has shown an increasing trend, especially in the last decade, in the management of esophageal malignancy. The aim of the present study was to present a cohort of patients who underwent MIE between June 2008 to June 2016 at a single tertiary care centre. Methods: A total of 103 esophagectomies were performed for esophageal malignancy which included 69 patients by minimally invasive technique. The procedure was performed by thoracoscopic mobilization of esophagus initially followed by reconstruction part done by either by minilaparotomy or by laparoscopic approach i.e. total thoracolaparoscopic esophagectomy (TLE). Results: The MIE was successfully completed in 65 (94.2%) patients. Operative time ranged from 275 to 420 min (average 356 min). The number of dissected lymph nodes were 5–15 (9 on average). The postoperative period was uneventful - without any complications in 36 (52.17%) patients. The most common postoperative complications were respiratory complications which were observed in 22 (31.88%) patients. Other complications included post-operative bowel obstruction (1 patient), anastomotic leak (4 patients), and necrosis of the gastroplasty (1 patient). One patient had chyle leak while cardiac complication was seen in three cases. The overall morbidity of patients underwent MIE was 47.8%. Thirty-day mortality was 5.79%. Conclusions: Esophagectomy performed by minimally invasive technique is a widely accepted surgical procedure for patients with middle and lower esophageal malignancy. The biggest benefit of MIE is avoidance of thoracotomy / laparotomy associated pain with resultant decrease in morbidity. The success of MIE requires a dedicated surgical team well trained in both MIE as well as in open surgical procedure.